La circoncision et l’excision en Éthiopie du XVe au XVIIIe siècle : lectures d’un rituel - Marie-Laure Derat (Afriques)
From an extract of the Maṣḥāfa Berhān written under the supervision of King Zar’a Yā‘eqob (1434-1468) which describes how female circumcision of the girls should be done according to the law of the Old Testament, this article analyses how the excision and the circumcision were related in the Ethiopian Church in the Fifteenth Century. But in the Seventeenth Century, when the Jesuits tried to convert the Ethiopian Kingdom to catholicism, they looked at the circumcision as Jewish practice and the excision as a pagan custom. To answer to this condemnation, the Ethiopians tried to justify themselves by keeping the link between circumcision and excision and considering them as customs and not Christian rites. This example shows how a rite could be read in different ways according to the stakes of the present.